Microwave Solid Phase Synthesis, Characterization and Antimicrobial Activities of Bis(5-chloro-2-hydroxybenzaldehyde)ethane-1,2-diamine-Zinc(II) - Xu, Suo-Ping; Yang, Xue (Asian Journal of Chemistry, 2015)
One mononuclear complex (1) has been designed and synthesized by bis(5-chloro-2-hydroxybenzaldehyde)ethane-1,2-diamine (L) with Zn(CH3COO)2·2H2O in microwave radiation assistance. The complex was characterized by X-ray crystallography, confirming that the central zinc(II) was coordinated by two oxygen atoms, two nitrogen atoms from L. The complex was assayed for in vitro antibacterial (B. subtilis, S. aureus, S. faecalis, P. aeruginosa, E. coli and E. cloacae) activities and showed better antimicrobial activity against Gram-positive strains than Gram-negative strains.